Service quality on patient expectation and actual service received at Gleanegal Kuala Lumpur - Nazratulshima, Mohd Halim (2016)
An improving patient satisfaction and service quality are very important in Gleneagles Hospital Kuala Lumpur. Although this hospital has increasingly number of patient but it is very important to understand patient needs and want and thus create long term and loyal customer. The aim of this study is to determine the relationship between patient expectations and actual service received towards the service offered. This is quantitative research method used to measure the five dimension of SERVQUAL model in service quality. Sample of three hundred and fifty set of questions paper used in this research distributed to inpatient and outpatient department in Gleneagles Kuala Lumpur. Results of the survey analysis revealed that there is a difference between pre and post service rendered to the patients. There is significant result in five dimension which is Assurance, Reliability, Responsiveness, Empathy. Nevertheless, there is no significant different result in Tangibility.